Optimization of Indonesia biodiesel production from rubber seed oil using natural zeolite modification - Junifa Layla Sihombing; Ahmad Nasir Pulungan; Poppy Lindawati; Adittiya Prayoga; Intan Ayu Safitri; Clara Nur Wandani; Lastri Anita Silitonga; Ambarwati Ambarwati; Puji Prayugo; Ary Anggara Wibowo (Jurnal Pendidikan Kimia (JPKim), 2018)
Abstract:       The purpose of this research is to find the optimization process of biodiesel production from rubber seed oil using natural zeolite modification. The method of this research are using 1) Modification of Natural Zeolite Using NH4NO3, 2) Characterization of catalyst using FTIR and XRD, 3) Esterification and transesterification of rubber seed oil at 30oC, 40oC, 50oC and 60oC for 2 hours in each step using H-Zeolite, and 4) Analyzation of liquid product using Gas Chromatography (GC). The result of this research shown that the best conversion of rubber seed oil into methyl ester fatty acid of about 76.43% with Methyl linoleate component reached 38.23% at 60oC. Moreover, the characterization of catalyst revealed that there is no a significant change in terms of mineral content and crystallinity between natural zeolite and its modification which are showed as mordenite with triclinic crystal system. In essence, H-zeolite can optimize the production biodiesel.Keywords:biodiesel; H-zeolite; natural zeolite modification; rubber seed oil